Analysis Of Kasir Applications In Sales Management Information Systems at ASRI Store - Nur Fatihatul Jannah; Muqorobin Muqorobin (Institut Teknologi Bisnis AAS Indonesia, 2021)
Abstract—Management Information System is an organized series of a number of parts/components that jointly function or move to produce information that is used in company management. Therefore the company needs an adequate system to produce valid information. As with UD Asri, the company is engaged in trading, whose company's activity is to sell various types of basic ingredients so that the company is overwhelmed in dealing with customer demands. With these problems, the company needs a system that can overcome the problems. Before there was a new system the company used a manual system which was very laborious, therefore the company needed a new system that would solve the problem. Finally, the company uses a cashier application system. So in this final project, we will discuss how the system in the cashier application works so that the company's activities can run. A cashier application is an application used in an office or business location where goods/services are sold to customers. With this application, all sales transactions can be stored properly.The research was conducted at UD Asri. The data collection method used is the method of observation, interviews and literature study. In making this report, of course, it cannot be separated from data analysis starting from planning to system testing. The model used in this application is the PIECES model (Performance, Information, Economy, Control, Efficiency, Service). The cashier application uses Visual basic programming language and the database used is Microsoft SQL server 2000. In this final project also provides information related to the company that is the object of research. This study shows the results of (1) knowing what is in the system so that the system can run, (2) knowing the process the system works, (3) the benefits obtained by the company from the application.